Analisis Hukum Fasilitas Penanaman Modal Bagi Investor di Kawasan Ekonomi Khusus - Agatha, Aurelia; Sona, Riska Suainur (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Indonesia's Special Economic Zones (SEZs) have long been under global scrutiny as they serve as a primary tool for developed nations to assert their influence in developing and underdeveloped countries. In Indonesia, SEZs have evolved from various forms of economic activities such as Free Trade Zones and Closed Zones Plus, yet they have not yielded significant benefits for the country and foreign investors. As a strategically located archipelagic nation, Indonesia finds it challenging to avoid global interactions due to its crucial geographical position and abundant natural resources. This research aims to analyze the legal framework governing investment facilities for investors in SEZs, focusing on investment regulations, legal protection for investors, and infrastructure development policies. A literature review analysis method is employed to evaluate the legal implications of investment in SEZs. The findings of this study provide a deeper understanding of the legal challenges facing investors in SEZs and offer policy recommendations to enhance legal certainty and investment potential in these areas. The contribution of this research is essential to the literature on investment law and SEZ development, providing valuable insights for policymakers, legal practitioners, and academics involved in SEZ management.